Tetrapyridinium mu-oxido-di-mu-sulfato-bis[chloridodioxidomolybdate(VI)] - Fernandes, José A. (2018)
The title salt, (C(5)H(6)N)(4)[Mo(2)Cl(2)O(5)(SO(4))(2)], comprises four pyridinium cations for each [(MoClO(2))(2)(mu-O)(mu-SO(4))(2)]4- anionic unit. The asymmetric unit consists of three aggregates of the empirical formula. The tetraanionic bimetallic molybdenum(VI) cluster is unprecedented and contains two sulfate and one oxide bridges. This structure constitutes the first example of a non-polymeric compound with terminal oxide, sulfate and halide ligands bonded to the same metal. The hydrogen bonds connecting the pyridinium cations to the molybdenum clusters are diverse, varying from strong and directional interactions to bifurcated bonds with a subsequent loss of directionality.